Objective perimetry and diabetic retinopathy progression: a 10-year follow-up study - Yibekal, Betelhem T.; Rai, Bhim B.; van Kleef, Joshua P.; Sabeti, Faran; Rohan, Emilie M. F.; Nolan, Christopher J.; Maddess, Ted (Frontiers in Endocrinology, 2026)
PurposeWe investigated 10-year retinal function changes in persons with type 2 diabetes (PWT2D) using the objectiveFIELD Analyser (OFA) to measure per-region sensitivity and response delay. We also examined which baseline measures predicted diabetic retinopathy (DR) progression.MethodsParticipants underwent a comprehensive anterior and posterior segment examination at both visits. Participants were examined by four OFA test methods differing in visual field eccentricity and test duration, each producing per-region sensitivities and response delays. DR severity was graded using Early Treatment of Diabetic Retinopathy Study (ETDRS) scores. A generalized linear mixed-effects logistic regression model identified predictors of DR progression over 10 years.ResultsAt the 10-year follow-up, 16 PWT2D (11 men, mean age 67.3 ± 11.9 years) were reexamined and more than half (10 participants) exhibited DR progression by at least one ETDRS severity level. Average total deviations of the OFA30 test showed progressive sensitivity loss, particularly in peripheral and nasal regions, whereas response delays demonstrated radially symmetric defects for both OFA30 and OFA15. Logistic regression revealed that regional reduced sensitivity and prolonged delays were significantly associated with higher odds of DR progression, alongside clinical factors such as blood glucose, diabetes duration, biothesiometry score, and baseline DR severity. For OFA30, an initial sensitivity loss of 10 dB in the nasal field produced odds of progression of 1.74× (SE 1.50× and 2.03×, p<0.001). Initial central field delays of 10 ms increased odds by 1.12× (SE 1.08× and 1.15×, p<0.001). Linear models further confirmed that DR severity was significantly associated with changes in OFA sensitivity and response delay.ConclusionThe OFA may provide a rapid and convenient method for monitoring and predicting DR progression. By assessing changes in retinal function, OFA shows potential as a valuable tool for tracking disease progression and may offer greater sensitivity for detecting functional changes over time.